2022
DOI: 10.3390/ma15072627
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Color Glass with High Light Transmittance by Pearlescent Pigments and Optical Adhesive

Abstract: In this study, we propose a solution process for realizing colored glass for building integrated photovoltaic (BIPV) systems by spin coating a color solution composed of pearlescent pigments mixed in a Norland Optical Adhesive (NOA) matrix. Color solutions are made from mixing pearlescent pigments in NOA63. Compared to a physical vapor deposition process, color coatings are achieved by spin coating in a relatively simple and inexpensive process at room temperature. The optical properties can be easily controll… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…EVA is essential for laminating solar panels and glass substrates in conventional color glass structures for BIPV systems, and it is an excellent adhesive that can passivate against external factors such as moisture and dust. It also has advantages such as high transmittance, UV resistance, and weather resistance [25], implementing the color with a color solution coating and not using additional adhesives to simplify the color realization and adhesion process using EVA, which is the existing BIPV color glass manufacturing method [26]. The transmittance of color glass made using optical adhesive is 85~90%, which is similar to the color glass proposed in this paper.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…EVA is essential for laminating solar panels and glass substrates in conventional color glass structures for BIPV systems, and it is an excellent adhesive that can passivate against external factors such as moisture and dust. It also has advantages such as high transmittance, UV resistance, and weather resistance [25], implementing the color with a color solution coating and not using additional adhesives to simplify the color realization and adhesion process using EVA, which is the existing BIPV color glass manufacturing method [26]. The transmittance of color glass made using optical adhesive is 85~90%, which is similar to the color glass proposed in this paper.…”
Section: Introductionsupporting
confidence: 59%
“…The transmittance of color glass made using optical adhesive is 85~90%, which is similar to the color glass proposed in this paper. In the case of the color glass using NOA as a matrix, NOA is used between the back sheet and the solar cell in the lamination process performed to make the BIPV module [26]. However, NOA requires strong UV radiation to be cured.…”
Section: Introductionmentioning
confidence: 99%
“…On the facades of 83 sqm, Kromatix TM blue, blue-green, grey, and brass are employed, shown in Figure 12f, which provides a stylish building-integrated thermal collector solution [115]. However, this technology is costly, time-consuming for color creation, and yields layers with poor transmittance [116,117] which is hard to be accepted by consumers. [111]), (e) bronze colored BIPV façade in a residential building in Zurich, Switzerland (reproduced and modified with permission from Ref.…”
Section: Colored Bipv Systems Status and Challengesmentioning
confidence: 99%
“…Solar cells (SCs) with low pollution and semi-permanent lifespans have been considered the most promising solution to meet the ever-increasing energy demand, and they are widely used in various industrial applications such as large power plants, small personal devices, batteries, super capacitors, and nano-generators [1][2][3]. Although many studies have been reported on high-efficiency organic and perovskite SCs, building-integrated photovoltaics (BIPV) have gained popularity in recent decades as a potential approach to reduce energy wastage and maximize efficiency in buildings [4][5][6][7]. 3 These authors contributed equally.…”
Section: Introductionmentioning
confidence: 99%
“…However, most SCs have very thick semiconductor layers to absorb as much incident light as possible, and they typically have a black or very dark blue color. Such dark and unattractive colors limit the aesthetic appeal of various surfaces where SCs are installed, including automotive surfaces, windows, and building surfaces, and they disturb harmony integration with the surrounding areas [4,8]. Therefore, it is important to develop color PV that can produce red, green, and blue over a broad spectrum while providing aesthetic utility.…”
Section: Introductionmentioning
confidence: 99%